Pengaruh Disiplin Kerja Staf Dan Tenaga Pengajar Terhadap Pencapaian Visi Dan Misi STIE Mujahidin Tolitoli - suparman stie; Nur Hafifah Huzairah (Fakultas Ekonomi Universitas Indonesia Timur, 2021)
School of Economics Mujahidin Tolitoli, is a private university located in Tolitoli Regency, Central Sulawesi Province, which was founded in 2001 which has produced alumni best that can compete with graduates from other universities but still have complaints from students about the performance of staff and teaching staff at these colleges. The purpose of this study was to determine how the influence of staff and teaching staff work discipline on the achievement of the vision and mission at STIE Mujahidin Tolitoli. In this study, the data were processed using descriptive and quantitative analysis, namely the Likert scale for descriptive needs and simple linear regression analysis for quantitative data. The results of this study indicate that the influence between the two related variables is 56% or positive, which means that work discipline determines the achievement of the vision and mission of STIE Mujahidin Tolitoli, the relationship between work discipline and the achievement of vision and mission has a unidirectional relationship. The conclusion in this study is that work discipline determines the achievement of the vision and mission of STIE Mujahidin Tolitoli.